2018
DOI: 10.1007/s11356-018-1369-8
|View full text |Cite
|
Sign up to set email alerts
|

Sonocatalytic degradation of rhodamine B in presence of CdS

Abstract: A novel sonocatalyst CdS was prepared by a facile precipitation method, and characterized by X-ray powder diffraction, transmission electron microscopy, UV-vis absorption spectroscopy, and photoluminescence spectroscopy. Comparative sonocatalytic degradation experiments were carried out in different conditions under ultrasonic irradiation and with rhodamine B (RhB) used as the model substrate. Results indicate that CdS is a highly active sonocatalyst. The efficiency of RhB sonodegradation in aqueous solutions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover, the efficiency was compared with related one reported in the literature and the values are depicted in Table S1 (ESI †). 23,26,41,[55][56][57][58][59][60][61][62][63][64][65][66][67] From the table, it is clear that the prepared AFO/WO 3 material shows good efficiency than the most of the materials reported for sonocatalytic degradation application.…”
Section: Sonocatalytic Degradation Analysismentioning
confidence: 99%
“…Moreover, the efficiency was compared with related one reported in the literature and the values are depicted in Table S1 (ESI †). 23,26,41,[55][56][57][58][59][60][61][62][63][64][65][66][67] From the table, it is clear that the prepared AFO/WO 3 material shows good efficiency than the most of the materials reported for sonocatalytic degradation application.…”
Section: Sonocatalytic Degradation Analysismentioning
confidence: 99%
“…The sonocatalytic degradation of organic pollutants using traditional sonocatalysts including Mo 2 O 3 , CdS, ZnO@Fe 3 O 4 , MoS 2 , and TiO 2 has been extensively researched in numerous studies [19][20][21][22][23]. Among various sonocatalysts, molybdenum disulfide (MoS 2 ) based materials are widely investigated because of their chemically stable nature, Earth-abundant tunable structure and nontoxicity [24].…”
Section: Photochemistry and Magnetochemistrymentioning
confidence: 99%
“…It was observed that sonocatalytic efficiency was improved by an increase in the catalyst concentration from 100 to 200 mg. This is due to more active sites are provided by enhancing the MG-20 dosage, which will come into being the more reactive radicals (-OH) [36]. MG-20 sonocatalytical performance was evaluated at 100 W power with the catalyst dose of 100 mg at different concentrations of MB (Fig.…”
Section: Sonocatalytic Degradation Of Methylene Blue (Mb) With Restacked Mos 2 Mg-10 and Mg-20mentioning
confidence: 99%
“…Organic dyes are one of the major pollutants in wastewater discharged from the food, textile, plastics, and cosmetics industries. , It is estimated that thousands of different dyes and pigments are used in industry, and a huge amount of synthetic dyes is produced annually worldwide. Pollutants emitted by the global textile industry continue to cause incredible harm to the environment, polluting land and rendering it useless and unproductive. …”
Section: Introductionmentioning
confidence: 99%